"I Was Proud of Myself That I Didn't Give Up and I Did It": Experiences of Pride and Triumph in Learning Science. Issue 4 (14th May 2015) - BELLOCCHI, ALBERTO; RITCHIE, STEPHEN M.
ABSTRACT The role that specific emotions, such as pride and triumph, play during instruction in science education is an underresearched field of study. Emotions are recognized as central to learning yet little is known about the way in which they are produced in naturalistic settings, how emotions relate to classroom learning during interactions, and what antecedent factors are associated with emotional experiences during instruction. Data sources for the study include emotion diaries, student written artifacts, video recordings of class interactions, and interviews. Emotions produced in the moment during classroom interactions are analyzed from video data and audio data through a novel theoretical framework related to the sociology of human emotions. These direct observations are compared with students' recollected emotional experiences reported through emotion diaries and interviews. The study establishes links between pride and triumph within classroom interactions and instructional tasks during learning episodes in a naturalistic setting. We discuss particular classroom activities that are associated with justified feelings of pride and triumph. More specifically, classroom events associated with these emotions were related to understanding science concepts, social interactions, and achieving success on challenging tasks.